ANALISIS BENTUK PERUNDUNGAN DAN PRAKTIK PENANGANAN GURU DI SD 67 PEKANBARU - Liza Lestari Roni Hamdani; Neni Hermita; M. Jaya Adi Putra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the various forms of bullying and the handling practices of teachers at SD 67 Pekanbaru, focusing on teachers’ meanings and experiences in addressing bullying phenomena in elementary school settings. Bullying in primary schools remains a critical issue in education as it directly affects students’ social and emotional development. The research employs a qualitative approach with a case study design, allowing for an in-depth and contextual understanding of the phenomenon. Data were collected through in-depth interviews, participatory observations, and document analysis, involving six classroom teachers selected purposively based on their direct involvement in handling bullying cases. The findings reveal that the most dominant forms of bullying are verbal and social-relational, such as teasing and peer exclusion. Teachers’ strategies in managing bullying focus on educational, dialogical, and empathy-based approaches, emphasizing moral reflection and interpersonal understanding among students. However, challenges remain in identifying non-physical forms of bullying and in the limited institutional support provided by the school. These findings highlight that teachers act as moral and social agents who not only enforce discipline but also foster empathy and a culture of mutual respect within the elementary school environment.